ANALISIS TINGKAT PEMAHAMAN RELASIONAL MATEMATIKA SISWA KELAS VIII MTSN - Muzdalifah, Muzdalifah; Ramli, Anwar; Kamarullah, Kamarullah; Darwani, Darwani (Mathieu : Journal of Mathematics Education and Learning, 2025)
His study aimed to determine students’ relational understanding of mathematics on solid geometry material in class VIII of MTsS Darul Ulum Banda Aceh. The study used a qualitative approach, with data collected through individual tests and interviews. The results showed that students had different levels of relational understanding based on their mathematical abilities. Students with high mathematical ability demonstrated high relational understanding by being able to connect concepts and solve problems correctly. Students with moderate mathematical ability showed moderate relational understanding with limited ability to relate concepts. Meanwhile, students with low mathematical ability demonstrated low relational understanding and experienced difficulties inunderstanding relationships between solid geometry concepts. These differences were identified through the indicators of relational understanding achieved by each student